Double Movements and Disembedded Economies: A Response to Richard Sandbrook. Issue 3 (8th February 2022) - Goodwin, Geoff
ABSTRACT: Richard Sandbrook (this issue) makes an important contribution to Polanyian debates in his typically insightful article on the double movement. However, his reading of the concept has limitations when used to analyse the historical evolution of capitalism and the current conjuncture. The merits and limits of his analysis are outlined in this article through the discussion of three core Polanyian concepts — disembedded economy, decommodification and countermovement. The article concludes by signposting the contribution Polanyian analysis can make to efforts to decolonize knowledge and reimagine the economy in the wake of the COVID‐19 pandemic.